New Improved Inequalities Associated with Ratios of Gamma Functions - Jenica Cringanu (Journal of Mathematics)
In this paper, we improve the estimate for the products ∏k=1n4k−3/4k and ∏k=1n4k−1/4k, obtained by Cringanu “inequalities associated with ratios of gamma functions.”